Explosive force - Eason, Lynette (Love inspired suspense., 2018)
Just before the K-9 training center explodes, reporter Heidi Jenks spots the bomber<U+2014>and now he wants her dead. While military explosives expert First Lieutenant Nick Donovan doesn<U+2019>t trust journalists, it<U+2019>s his duty to protect Heidi. And with a killer circling closer, he and his bomb-sniffing K-9 are all that stands between Heidi and someone planning to silence her for good.